Kinaesthetic empathy through the lens of the cinematographer: physiological and phenomenological alignments in the act of creation - Primett, William; Mukhina, Ksenia; Burak Yilmaz, Mehmet; Rietdijk, Willeke; Tikka, Pia (Frontiers in Neuroscience, 2025)
Film and actor-driven narratives showcase a structured and authentic depiction of emotions, and are considered a reliable resource for validating affective states when coupled with physiological data. In affective computing studies, emotional engagement is often portrayed and perceived as a single-directional mode of interaction between the viewer and the elicitation material. We design a study from the perspective of the cinematographer, who is actively engaged in the creation of the source material while witnessing it. Thus, the image emerges in the interaction between the cinematographer “reading” the actors during the filming, and visa-versa. The captured movement, physiological data, and first-person accounts are gathered from six participants and organized into a multimodal dataset. From this, we introduce a phenomenological data explorer framework, a visualization tool that's used to assess the affective and motor responses during the filming process, while considering the phenomenological experience and narrative immediacy. In turn, we draw triangulations between visual perception, sensorimotor patterns and narrative structures to inform the bidirectional nature of empathic engagement in cinematic storytelling. Our findings emphasize the role of kinaesthetic empathy, in which embodied decision-making responds to predicted inner states, shaping and modulating emotional understanding throughout the filming process.